Peningkatan Kasus Kondiloma Akuminata pada Remaja Berkaitan dengan Personal Hygiene dan Pengetahuan Kesehatan Reproduksi - Sekar Rahmadhanti; Yani Achdiani (Jurnal Kendari Kesehatan Masyarakat, 2025)
Condyloma acuminata, caused by infection with Human Papillomavirus (HPV) types 6 and 11, is one of the most common sexually transmitted diseases in adolescents. This study aims to analyze the relationship between personal hygiene and reproductive health knowledge with the increase in cases of condyloma acuminata among adolescents. The method used is qualitative based on literature studies and content analysis of health education on social media, especially TikTok. The results of the study showed that adolescents with good knowledge of genital hygiene and prevention of sexually transmitted infections tend to have better preventive behaviors. In addition, poor personal hygiene contributes to an increased risk of HPV infection. The conclusion of this study emphasizes the importance of adequate health education to reduce the incidence of condyloma acuminata among adolescents